Quantitative Structure-Property Relationship Analysis of Thiosemicarbazone Derivatives with Antimalarial Activity and Some Therapeutic Compounds Using Leap Indices - Sri, B. Roopa; Naidu, Y. Lakshmi (Communications in Mathematics and Applications, 2025)
In this article, we perform the QSPR analysis of two datasets of therapeutic compounds using topological indices. The least explored category of indices is chosen for this study. They are the leap indices, namely \(F\)-Sombor, modified \(F\)-Sombor, reduced Sombor, second \(F\)-Sombor, Sombor, modified Sombor, \(F\), and \(F_1\) leap indices. We have considered some thiosemicarbazone derivatives that are tested for their antimalarial activity in one dataset and some randomly chosen drugs in another dataset. We investigate the correlation between a few leap indices and some physicochemical properties of these two datasets separately using machine learning techniques.
Keywords: QSPR analysis; F-Sombor leap index; Second F-Sombor leap index; Modified F-Sombor leap index; Reduced Sombor leap index